ANALISIS EKSPERIMENTAL GETARAN BANTALAN BOLA DENGAN MENGGUNAKAN FRF ORDE TINGGI - Trihono Sewoyo; Komang Bagiasna; Zainal Abidin (Mesin, 2000)
This work is based on method developed by Storer, Lee and Tomlinson [1,2,3]. Storer [1] determined parameter of nonlinear system by curve fitting of higher order FRF that was obtained by measuring stimulus and response of nonlinear system in the frequency domain. While Lee [2] determined spatial model parameter i.e. mass, stiffness and damping constant based on higher order FRF that was obtained from measurement of excitation force amplitude in time domain and complex response in frequency domain. In this paper the two methods will be compared by conducting experiment on the ball bearing which shows nonlinear behavior [4,5]. The result shows the two methods have a signiï¬cant difference. While the amplitude of excitation force affect the higher order Transfer Function and also the dynamical parameter of the system.